“Vascular Lock” Causing Splenic Perfusion Defects During Irreversible Electroporation of a Locally Advanced Pancreatic Tumor - Ierardi, Anna Maria; Lucchina, Natalie; Duka, Ejona; Bacuzzi, Alessandro; Dionigi, Gianlorenzo; Carrafiello, Gianpaolo (JOP. Journal of the Pancreas, 2014)
Context There is little reported experience of irreversible electroporation (IRE) of locally advanced pancreatic tumors (LAP). In literature, few data reported complications. In particular vascular vasoconstriction miming splenic infarcts in humans has never been found. Case report This report describes the onset of asymptomatic multiple little splenic perfusion defects after the treatment of a LAP localized in the boby-tail portion of the pancreas with the application of five percutaneous probes for IRE, in a 79 year-old man. Splenic artery was regularly patent but entirely trapped in the tumor. Conclusion To the best of our knowledge, until now, no experience concerning percutaneous IRE of pancreatic cancer described that phenomenon. The cause could not be established with certainty and “vascular lock" may be a valid hypothesis. Additional studies are necessary to evaluate its frequency and its exact pathophysiological cause in humans. Image: Splenic parenchyma before irreversible electroporation at coronal CT.